THE A-TYPE KERKINI GRANITIC COMPLEX IN NORTH GREECE: GEOCHRONOLOGY AND GEODYNAMIC IMPLICATIONS - Christofides, G.; Koroneos, A.; Liati Α.; Kral, J. (Bulletin of the Geological Society of Greece, 2007)
The Kerkini granitic complex (KGC) intrudes the Serbomacedonian massif KGC comprises the Mûries granite (MUR), the Miriofito granite (MIR), and the Kastanusa (KAS) granodiorite. The main rock-type is two-mica granite. Feldspars are represented by albite andperthitic microcline, biotite is iron-rich and white mica is phengite. Fluorite is also present. The rocks are peraluminous, enriched in total alkalis, depleted in MgO and CaO and have high FeOt/MgO ratios. They are enriched in Zr, Nb, Y, Ga and REE, and have strong negative Eu anomaly. They plot in the Atype granite fields of various discriminant diagrams and their chemistry suggests a WPG tectonic environment. Sr initial ratio ranges from 0.7107 to 0.7182. The most probable genetic model is fluid-absent melting of a biotite-rich tonalitic crustal source at 950 -975 C and at considerable depths. Rb-Sr white mica ages and SHRIMP U-Pb zircon ages yielded 246±3 Ma and 247±2Ma, respectively, interpreted as the crystallization age of the KGC. K-Ar ages of 130±3 and 131 ±3 Ma (biotite) and 133±3 Ma (white mica) can be interpreted by a metamorphic/fluid event at about 133 Ma. Rb-Sr white mica dates at 152±2 Ma probably resulted by incomplete resetting of the Rb-Sr isotopie system and yielded "mixing ages" between crystallization (ca. 247 Ma) possibly related to a Permian - Triassic rift event and metamorphic/fluid event (ca. 133 Ma).